The Effects of Mothers' Anxiety Level and Obsessive and Compulsive Behaviors Regarding Baby Care on Breastfeeding Motivation in the Postpartum Period - Sema Yılmaz; Süreyya Kılıç (Ebelik ve Sağlık Bilimleri Dergisi)
Objective: The study was planned to investigate the relationship between mothers' anxiety and obsessive and compulsive behaviours related to baby care and breastfeeding motivation in the postpartum period.Methods: The sample of the descriptive and correlational study consisted of 367 mothers who applied to the pediatric clinic of a state hospital in the Central Anatolia region between November 2022 and June 2023 for control purposes. The data were collected using Personal Information Form, Primiparous Breastfeeding Motivation Scale (PBMS), Postpartum Specific Anxiety Scale (PSAS) and Obsessive and Compulsive Behaviours of Mothers Towards Baby Care in the Postpartum Period Scale (PPOCBS). Descriptive statistics, independent groups t test, One-Way ANOVA test and Pearson correlation analysis were used to analyse the data.Results: The mean scores of PSAS and PPOCBS the mothers who participated in the study were 112.33±3.90, and 26.36±10.80, respectively. The mean scores of the value ascribed to breastfeeding, self- effectiveness, midwife support and expectation of success sub-dimensions of the PBMS scale were 77.19±17.43, 41.71±9.71, 20.19±7.64 and 10.84±6.20, respectively. It was determined that there was a significant relationship between the total mean score of the PSAS and the sub-dimension scores of value ascribed to breastfeeding and success expectation levels of the PBMS. It was found that there was a significant relationship between the mean score of the mothers' PPOCBS and the mean score of the value ascribed to breastfeeding sub-dimension of PBMS.Conclusion: In the postpartum period, as value ascribed to breastfeeding increases, anxiety increases and success expectancy decreases. As the PPOCBS increases, value ascribed to breastfeeding decreases.